The Effective Communication through Climate Change Campaign in Sustainable Port Development - Susana Emyliasari; Diandita Amelia Permadani; Aliffia Yulitarahmi (Jurnal Spektrum Komunikasi, 2024)
Port development has an impact on climate change. A sustainable port as a solution to the problem focuses on three pillars: economic, social and environmental. This article explores and analyses the challenges to the development of sustainable development of PT Pelabuhan Indonesia (Pelindo), using PT Terminal Petikemas Surabaya (TPS) as a case study. Our aim in this study is to highlight the importance of two pillars, namely environmental and social in the concept of sustainability. This study analyses the environmental climate change campaign conducted by TPS. The researcher used a qualitative descriptive approach to conduct the case study. Data were collected through interviews and observations as primary data, while internal company data, documentary films, internet media coverage, and literature studies became secondary data. The research revealed the company's communication process by collecting information regarding the number of impressions received from news coverage and social media reports. Since TPS has not determined a standardised score, the communication process needs a more comprehensive evaluation. TPS should focus on this area further to determine the effectiveness of its current communication strategy.